Impact of second phase content over rheological behaviour of rock salt under cyclic loading conditions applied to Underground Gas Storage - Martin-Clave, Carla (2021)
The use of caverns in rock salt for Underground Gas Storage (UGS) and Compressed Air Energy Storage (CAES) have been identified as a strategic option to meet seasonal energy demand fluctuations in the electricity grid. More recently, the Department for Business, Energy and Industrial Strategy (BEIS) presented for the UK Clean Growth strategy a plan to also integrate rock salt caverns as a storage solution for co-located carbon capture, utilisation and storage (CCUS) and hydrogen production. The creation of caverns in halite formations and the operational activities of gas injection and withdrawal occurring under lithostatic pressure are known to lead to local deviatoric stresses, resulting in rock salt creep deformation. Additionally, periodic injection-production activities in response to seasonal temperature changes and associated gas consumption imply regular fluctuation of both mechanical and thermal stresses in salt caverns. Rock salt is mainly composed of halite and has low i) creep strength, ii) porosity, iii) permeability, and iv) density, making it a very good seal rock to store gas. It also typically contains secondary mineral phases (e.g. anhydrite, polyhalite, carnallite, kieserite), as well as fluids trapped in inclusions in the halite crystals, at halite grain boundaries, or in pores. This presence of other minerals besides halite, or other rock layers between the rock salt formations at a range of scales, can have significant effects on the micro and macro-mechanical properties due to their different rheological behaviours, notably weakening the rock salt under high-stress conditions. This project investigates the impact of the secondary mineral phase content on the rock salt mechanical behaviour under cyclic loading conditions. A series of cyclic mechanical loading experiments, at two different ranges of cyclic mechanical load, have been performed on different rock salt samples with different types and amounts of second phase minerals content. In the first set of tests, different confining pressures of 12, 25 and 45 MPa and different temperatures, of 22-25, 55 and 75ºC, have been applied whilst the axial stress was cycled between 4.5 and 7.5 MPa, at 0.5 kN/s loading rate, during 48h (7200 cycles). In the second set of experiments, the axial stress was cycled between 6 and 20 MPa, at 0.5 kN/s loading rate, during 48h (7200 cycles) and confining pressures of 25 and 45MPa and temperatures of 22-25, 55 and 75ºC. Thin sections of each sample's microstructures, before and after mechanical deformation, were analysed by transmitted light microscopy and Scanning Electron Microscopy (SEM) to identify the micro-mechanisms and early damage induced by the cyclic loading conditions. The results demonstrate that high second phase content such as anhydrite layering operates as a strength weakening agent by displaying larger brittle deformation features in comparison to samples with a lower content in anhydrite, polyhalite or clay as second phase content. This rheological behaviour is further exacerbated by the cycling mechanical conditions and recorded by a marked step on Young's modulus and Poisson's ratio value evolution. The microstructure analysis reveals how halite grains accommodate most of the deformation induced by the cyclic mechanical loading conditions through brittle deformation with micro-fracturing network development. Other structures from different deformation mechanisms are also discussed. Two types of new porosity are observed: i) pores around isolated crystals of second phase minerals as a result of grain rotation under cyclic mechanical deformation, and ii) micro-cracks in areas with a high concentration of secondary minerals (such as anhydrite, polyhalite, carnallite or kieserite). This porosity change has strong implications for both the mechanical behaviour of the material and its potential permeability.